Tingkat Kepuasan Mahasiswa pada Proses Belajar Mengajar Jarak Jauh - Dewi Suliyanthini; Annisa Zahra Irwan; Harsuyanti Lubis; Vivi Radiona (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The pandemic that has hit the whole world requires the teaching and learning process to becarried out online or distance learning, by utilizing information technology, electronic media as amedium for delivering learning materials during a pandemic and during social restrictions.Descriptive Quantitative Research Methodology by conducting a survey to students of the FashionDesign Education Study program, Faculty of Engineering – State University of Jakarta, Class of 2017to Class of 2021, with a population of 289 students, calculations using the Slovin sample formularesulted in a sample of 145 students. The results of the study, resulted in the level of studentsatisfaction in the online distance learning process which includes Empathy: 28%, responsiveness32%, certainty 21%, reliability 19%. This shows that the delivery of lecture material online is lessthan optimal